The constitutional and statutory position of the 'other' wife: a comparative study of constitutional rights and polygamous customary marriages in Commonwealth Africa - Cotton, Sonya (Department of Private Law, 2018)
In the context of a perceived globalisation of human rights, this thesis considers whether constitutional rights to equality and non-discrimination apply to polygynous customary marriages in Commonwealth Africa from a legislative perspective. In other words, I examine whether there is a correlation between constitutional protection of rights and legislation, sensitive to the human rights of women in polygynous customary marriages. It is shown that at a constitutional level, there is often a strong indication that human rights to equality and non-discrimination apply to customary laws, including customary institutions of marriage. This, however, often does not translate to a statutory level, resulting in marriage laws that largely side-line and ignore the possibility of polygyny in a customary marriage and the potential for human rights violations therein. I analyze the discursive mechanisms that facilitate the contradiction that arises when constitutional commitments to protect the rights of women in polygynous marriages are not met at a legislative level. I argue that practices of 'silence' and 'omission' are used to perpetuate the myth that monogamy is the default position of all marriages governed by statute. This effectively constructs polygynous marriages as an aberration to the norm, and further renders invisible the parties in polygynous customary marriages. In failing to provide statutory guidance for the complexities that may arise in polygynous marriages, I argue that women in polygynous marriages are discriminated against in comparison to women in monogamous relationships.